A Rare Hb H Hydrops Fetalis Syndrome Caused by the – –SEA Deletion in Combination with the Rare Hb Hirosaki Mutation in a Chinese Patient. (4th July 2018) - Li, Qiang; Li, Yihong; Zhong, Mei; Zhang, Victor Wei; Jin, Wangjie; Li, Shaoyuan; Li, Liyan
Abstract: Despite the milder clinical severity of Hb H patients compared with those of Hb Bart's hydrops fetalis or patients with β-thalassemia major (β-TM), a few cases of Hb H hydrops fetalis syndrome have been reported so far. Here, we describe, for the first time in the Chinese population, one case of a neonate with Hb H hydrops fetalis syndrome caused by the – – SEA (Southeast Asian) deletion in combination with the Hb Hirosaki ( HBA2 : c.132C>G, p.Phe43Leu) mutation. Our study highlights the importance of continuous fetal monitoring using ultrasonography and blood screening studies of fetuses. Appropriate genetic counseling and comprehensive clinical follow-up should be performed on a pregnant woman who carried an α 0 -thalassemia (α 0 -thal) deletion and had a Hb H or Hb Bart's hydrops fetalis offspring, especially if the woman's partner also carried a hemoglobinopathy.